Investigations on energy conservation of waste coconut water through an up-flow anaerobic hybrid bioreactor - DAYANAND KUMBAR; Dr. Shaji James P (Guide) (Tavanur 2016 DEPARTMENT OF FARM POWER, MACHINERY AND ENERGY)
Investigations on energy conservation of waste coconut water through an up-flow anaerobic hybrid bioreactor
Investigations on energy conservation of waste coconut water through an up-flow anaerobic hybrid bioreactor